Preparation and mechanical properties of palm fiber/polylactic acid composites - Hatta, Nasrul (2007)
In recent years, the demand for environmental friendly materials based on biodegradable polymer and natural fiber has growth interest. In this work, a biodegradable composite from polylactic acid (PLA) and oil palm empty fruit bunch (palm fiber) were prepared by compression moulding. However there were several limitations especially related to the fiber-matrix adhesion. So the palm fibers were treated by y -aminopropyl trimethoxysilane (APS) and methyl trimethoxysilane (MS) and also coated by polylactic acid (pLA) in varied percentage (5%, 10% and 15%). The effect of APS and MS treatment and PLA coating on the mechanical and dynamic mechanical properties of PLAIpalm fiber composites was examined. Thermogravimetric analysis showed the decomposition temperature of palm fiber was shifted to higher when treated by APS and MS. The density and flexural properties of composites were found to increase with increasing fiber coating and increased by introduction of APS and MS treatment. From dynamic mechanical analysis, it was also observed that the APS, MS treated fibers and PLA coating fibers have improved the dynamic mechanical properties of the composites respectively. The fiber-matrix morphology in the untreated and treated composites was confirmed by SEM analysis of fracture samples. The micrograph showed the improvement of fiber-matrix adhesion by incorporation of APS and MS fiber treatment.